Service attributes of Graduate Research Students needs in a Malaysian University. - Ismail, Affero; Zainal Abiddin, Norhasni (Journal of International Social Research, 2009)
Issues of graduate studies have been studied and debated worldwide in the face of a changing higher education landscape. There are various stakeholders in the graduate process of study and inquiry, including the wider macro socio-economic environment, the micro institutional and departmental environment, as well as the individual student. Students need information and support to cope in balancing the demands of the different environments. This paper is mainly focusing on graduate research students’ needs in terms of information and services. Questionnaire was administered to graduate research students in a Malaysian public university. 184 (53.96%) sets of questionnaires were successfully returned from 341. Students’ responses in terms of information and services were reported. The study revealed that the information and services in this university was moderate from students’ perspective. Their needs and expectations were also being sourced. The results obtained show that graduate students’ needs extend beyond the mere informative basics. Suggestions were made on how the students’ stated needs can be used in the enhancement of an effective resource. As an educational institution, they may need to consider various ways in which these needs can be met. Students have different needs at the different level of graduate studies. The learning that takes place during graduate studies is a maturing process. Thus, effective resources are required in order to enhance the graduate process.